2017
DOI: 10.1590/1807-1929/agriambi.v21n3p163-168
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and grain yield of oats by growth regulator

Abstract: The use of growth regulator in oats can reduce plant lodging with reflections in biomass and grain yield. The objective of the study was to determine the feasibility and efficiency of using Trinexapac-Ethyl regulator in the growth of white oat under different conditions of N-fertilizer and years favorable and unfavorable for cultivation. In this study, two experiments were conducted in the years 2011, 2012 and 2013, one for quantifying biomass production rate and the other for the determination of grain yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…It was observed that only the treatment E1 resulted in lower plant height (p < 0.05), probably due to small amount of nutrients applied during this treatment. An effective way of controlling the lodging of white oats without interfering with their yield is to use growth regulators (Marolli et al 2017). In addition, the use of small-sized plants and regionallyadapted genotypes may decrease lodging of the crop.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that only the treatment E1 resulted in lower plant height (p < 0.05), probably due to small amount of nutrients applied during this treatment. An effective way of controlling the lodging of white oats without interfering with their yield is to use growth regulators (Marolli et al 2017). In addition, the use of small-sized plants and regionallyadapted genotypes may decrease lodging of the crop.…”
Section: Resultsmentioning
confidence: 99%
“…The harvest index is an important indicator of productivity, dimensioning how much of the total biomass produced was directed to the elaboration of biomass straw and biomass grains [20]. Seed density [20], nitrogen fertilization [5] and growth regulator [6] are the main management factors that affect the expression of the harvest index of oats. Reference [2] point out that the reduction in the oat harvest index in favorable year to cultivation is due to the greater favoring of the expression of the vegetative growth, although the grain productivity also increased, therefore, justifying that the increase in grain productivity does not express a behavior similar to that of the biological productivity, reducing the harvest index due to the higher volume of biomass straw.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [2] point out that the reduction in the oat harvest index in favorable year to cultivation is due to the greater favoring of the expression of the vegetative growth, although the grain productivity also increased, therefore, justifying that the increase in grain productivity does not express a behavior similar to that of the biological productivity, reducing the harvest index due to the higher volume of biomass straw. In wheat [28] and oats [6], the growth regulator increased the expression of the harvest index by the reduction of the straw biomass and the shortening of the stem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations